Penyuluhan Anti Narkoba Berbasis Spiritual Islam - Miftahul Ula; Amat Zuhri; Cintami Farmawati (University of Merdeka Malang, 2020)
Islamic spiritual based anti-drugs counseling is a program of community empowerment activities in Sufism and psychotherapy that aims to increase teacher and community knowledge in preventing drug abuse among students in Batang District. Community empowerment activities through Islamic spiritual-based anti-drug counseling use discussion methods, lectures with audiovisual media, and role playing. The number of respondents was 20 teachers of guidance counseling and 10 community leaders. The results of the activity obtained an increase in the knowledge of guidance counseling teachers and community leaders from 13% to 83% in the good category. In addition, indicate the benefits of Islamic spiritual based anti-drug counseling on the knowledge of guidance counseling teachers and community leaders. Activities undertaken include: providing an understanding of the dangers of drug abuse; do role playing cure drug addicts through Islamic spirituality with Qolbu Brain Rejuvenation (ROQ) techniques, and conduct monitoring and evaluation. Islamic spiritual based anti-drugs counseling activities are considered effective and can be used as an alternative preventing drug abuse in Batang Regency.DOI: https://doi.org/10.26905/abdimas.v5i2.4059